The Effect of Service Quality on Financial Performance and Satisfaction of Cooperative Members in Gianyar Regency - Ni Nyoman Alit Purnami; I Ketut Suamba; Ratna Komala Dewi (Journal of Sustainable Development Science, 2024)
This study aims to determine the effect of service quality on financial performance and member satisfaction as well as the level of profitability in Amertanadi Farmer Cooperative and Lumbung Sari Farmer Cooperative. The data collection method uses the interview method with a questionnaire as the main instrument in the research. The sample used in this study were members or family members of the Amertandi Tani Cooperative totalling 81 respondents and members of the Lumbung Sari Tani Cooperative totalling 86 respondents. The research data were obtained from the results of filling out the questionnaire and analysed using SEM analysis techniques with the help of the SmartPLS program. The results of this study indicate that service quality (tangible, reliability, responsiveness, assurance and empathy) has a positive and significant effect on financial performance and financial performance has a positive and significant effect on member satisfaction, based on the results of the study, it is hoped that the Amertandi Farmer Cooperative and Lumbung Sari Farmer Cooperative will be able to improve service quality so that members feel very satisfied.